Keputusan dan Preferensi Konsumen: Pinang Kering Iris di Perbatasan (Studi Kasus: Kabupaten Timor Tengah Utara) - Jemai, Yoseph Daniel; Sipayung, Boanerges Putra; Nubatonis, Agustius; Septiadi, Dudi (JURNAL MANAJEMEN AGRIBISNIS (Journal Of Agribusiness Management); Vol 10 No 2 (2022): Jurnal Manajemen Agribisnis, 2022)
Betel nut consumption in North Central Timor Regency lasted a long time and continues to grow to this day. The study aims to determine the factors that influence consumer decisions and consumption preferences of iris dried betel nut in north Central Timor border communities. This research was conducted in January-February 2022.The data analysis method used is qualitative descriptive and logistic regression analysis. The variables of age, sex, habits, taste, and texture together affect the consumption preferences of iris dried betel nut. The age and texture of the iris dried betel nut significantly affect the decision of the people of East Miomaffo Subdistrict in consuming slice dry betel nut. Texture becomes the preference of consumers to choose the dried betel nut of the iris consumed.